Tomographic reconstruction of two-dimensional radiated power distribution during impurity injection in KSTAR plasmas using an infrared imaging video bolometer - Jang, Juhyeok; Choe, Wonho; Peterson, B.J.; Seo, D.C.; Mukai, K.; Sano, R.; Oh, S.; Hong, S.H.; Hong, Joohwan; Lee, H.Y. (Current applied physics, 2018)
Based on the two-dimensional radiation images obtained by an infrared imaging video bolometer (IRVB) with tangential view, the two dimensional radiation profiles of plasmas in KSTAR were reconstructed. The IRVB installed on KSTAR has a tangential view of the plasma, and thus tomographic reconstruction of the raw images of radiation profiles was performed to remove the chord-integration effect by using a tomographic reconstruction code based on the Phillips-Tikhonov algorithm. Phantom reconstruction tests with various synthetic images were carried out to validate the accuracy of the reconstruction results. It is found that hollow radiation phantoms with strong divertor radiation were reconstructed with high accuracy. Furthermore, the effects of the number of channels of the IR camera, and the number of pixels of the plasma and of the IRVB on reconstruction performance are studied with phantom tests. Two-dimensionally reconstructed images of KSTAR plasmas demonstrated that radiation loss at the plasma edge and near the divertor region increased significantly after gaseous impurity injection. The total radiated power was up to 1.2 MW at the disruption, which was 40% of the NBI power. After argon and krypton gas injection, total radiated power was increased by 325 kW and 180 kW, respectively. •The tomography code forthe infrared imaging video bolometer in KSTAR was developed to reconstruct plasma emissivity.•The effects of IRVB hardware on reconstruction performance are investigated by phantom reconstruction tests.•Total radiated power of KSTAR plasmas can be calculated using the two-dimensionally reconstructed emissivity.•The emissivity at both the plasma core and the divertor increased significantly due to gaseous impurity injection.